Can transplant renal scintigraphy predict the duration of delayed graft function? A dual center retrospective study. - Stan Benjamens (PLoS ONE, 2018)
This study focused on the value of quantitatively analyzed and qualitatively graded renal scintigraphy in relation to the expected duration of delayed graft function after kidney transplantation. A more reliable prediction of delayed graft function duration may result in a more tailored and patient-specific treatment regimen post-transplantation.From 2000 to 2014, patients with early transplant dysfunction and a Tc-99m MAG3 renal scintigraphy, within 3 days post-transplantation, were included in a dual center retrospective study. Time-activity curves of renal scintigraphy procedures were qualitatively graded and various quantitative indices (R20/3, TFS, cTER, MUC10) were combined with a new index (Average upslope). The delayed graft function duration was defined as the number of days of dialysis-based/functional delayed graft function.A total of 377 patients were included, with a mean age (± SD) of 52 ± 14 years, and 58% were male. A total of 274 (73%) patients experienced delayed graft function≥ 7 days. Qualitative grading for the prediction of delayed graft function≥ 7 days had a sensitivity and specificity of respectively 87% and 65%. The quantitative indices with the most optimal results were cTER (76% sensitivity, 72% specificity), and Average upslope (75% sensitivity, 73% specificity).Qualitative renal scintigraphy grading and the quantitative indices cTER and Average upslope predict delayed graft function ≥ 7 days with a high sensitivity. This finding may help to support both clinicians and patients in managing early post-operative expectations. However, the specificity is limited and thus renal scintigraphy does not reliably help to identify patients in whom the course of delayed graft function is longer than anticipated.